2009
DOI: 10.1128/iai.00287-09
|View full text |Cite|
|
Sign up to set email alerts
|

Viral Booster Vaccines Improve Mycobacterium bovis BCG-Induced Protection against Bovine Tuberculosis

Abstract: Previous work with small-animal laboratory models of tuberculosis has shown that vaccination strategies based on heterologous prime-boost protocols using Mycobacterium bovis bacillus Calmette-Guérin (BCG) to prime and modified vaccinia virus Ankara strain (MVA85A) or recombinant attenuated adenoviruses (Ad85A) expressing the mycobacterial antigen Ag85A to boost may increase the protective efficacy of BCG. Here we report the first efficacy data on using these vaccines in cattle, a natural target species of tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(177 citation statements)
references
References 46 publications
12
161
4
Order By: Relevance
“…Further, vaccination experiments in non-human primates have associated a distinctive cytokine profile including IL-6 with protection (Reed et al 2009), whilst a recent mouse study has emphasized its role in the establishment of local innate responses after TB subunit vaccination (Hall et al 2010). IL-6 also promotes murine and (to a lesser degree) human TH17 cell differentiation (de Jong et al 2010), a T-cell subset recently linked to protection against tuberculosis (Khader et al 2007;Vordermeier et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Further, vaccination experiments in non-human primates have associated a distinctive cytokine profile including IL-6 with protection (Reed et al 2009), whilst a recent mouse study has emphasized its role in the establishment of local innate responses after TB subunit vaccination (Hall et al 2010). IL-6 also promotes murine and (to a lesser degree) human TH17 cell differentiation (de Jong et al 2010), a T-cell subset recently linked to protection against tuberculosis (Khader et al 2007;Vordermeier et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Significant IL-17 responses are elicited by M. tuberculosis infection of mice (42) and humans (43,44), as well as M. bovis infection of cattle (7,11). With M. tuberculosis infection of mice, early expression of IL-17 in response to vaccination is required for the rapid accumulation of protective memory cells in the lungs (45).…”
Section: Discussionmentioning
confidence: 99%
“…While TSTs are the mainstays for bovine TB antemortem testing, blood-based tests are attractive, as they require only a single visit to the farm, provide the opportunity for immediate repeat testing, and yield results that are less subjective than those of TSTs. Additional biomarkers have recently emerged as potential candidates for use in blood-based TB tests for humans (reviewed by Walzl et al [5] and Salgame et al [6]) and cattle, including interleukin-1␤ (IL-1␤), IL-2, tumor necrosis factor alpha (TNF-␣), nitric oxide, IL-17, and IFN-␥-induced protein 10 (IP-10) (7)(8)(9)(10)(11)(12)(13). Of these, IL-17 is particularly appealing as a biomarker for bovine TB, as IL-17A mRNA responses determined using real-time quantitative PCR (RT-qPCR) may be predictive of both vaccine efficacy (11,14,15) and lesion severity (7) when measured after vaccination and infection, respectively.…”
mentioning
confidence: 99%
“…48 With the support from Aeras, the OxfordEmergent Tuberculosis Consortium developed this virally vectored TB vaccine. As a heterologous boost for BCG, MVA85A moderately improved BCG-induced protective efficacy against M. tuberculosis challenge in animal models, [49][50][51][52] which was predominantly attributable to better induction of CD4 and CD8 T cell responses, as well as antigen-specific Th1 and Th17 cells responsible for protection against M. tuberculosis. 53 Several clinical trials have demonstrated that MVA85A appears to be safe and well tolerated.…”
Section: Mva85a(aeras-485)mentioning
confidence: 99%